Factors associated with quality of life and mood in adults with strabismus. Issue 4 (3rd January 2014) - McBain, Hayley B; MacKenzie, Kelly A; Au, Charis; Hancox, Joanne; Ezra, Daniel G; Adams, Gillian G W; Newman, Stanton P
Abstract : Background/Aims: To explore the factors associated with the mood and quality of life (QoL) of patients with strabismus due to undergo realignment surgery. Methods: A cross-sectional study was undertaken with adult patients. Along with demographic, clinical and psychosocial process variables, the Hospital Anxiety and Depression Scale and AS-20 QoL measures were administered. Regression models were used to identify the factors associated with QoL and mood. Results: Of the 220 participants, 11% were experiencing clinical levels of depression, and 24% clinical anxiety. This is in line with other forms of facial disfigurement but higher than other chronic diseases. Although mood and QoL were associated with age and diplopia, it was beliefs and cognitions which were more consistently associated with well-being. This included feelings of social anxiety and avoidance, a belief that strabismus has negative consequences, poor understanding of strabismus, social support, fear of negative evaluation and the perceived visibility of their condition. Conclusions: Psychosocial rather than clinical characteristics were identified as determinants of well-being in this population. It is important for clinicians planning surgery to be aware of these factors which could influence outcomes. Longitudinal studies need to be conducted to explore the direction of causality before interventions to improve well-being are developed and evaluated.